2021
DOI: 10.1016/j.clon.2021.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Modification of Hypoxia

Abstract: Regions of reduced oxygenation (hypoxia) are a characteristic feature of virtually all animal and human solid tumours. Numerous preclinical studies, both in vitro and in vivo, have shown that decreasing oxygen concentration induces resistance to radiation. Importantly, hypoxia in human tumours is a negative indicator of radiotherapy outcome. Hypoxia also contributes to resistance to other cancer therapeutics, including immunotherapy, and increases malignant progression as well as cancer cell dissemination. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 204 publications
0
11
0
Order By: Relevance
“…Over the recent decades, several hypoxia modification strategies have been developed and investigated in an attempt to improve patient outcomes (reviewed by Horsman et al [ 35 ]), however, most reported improvements in outcomes are modest due to the heterogeneity in hypoxia distribution, lack of hypoxia assessment and poor patient selection and stratification in clinical studies [ 14 , 36 ]. One early approach aimed to increase oxygen delivery to tumours by allowing patients to breathe hyperbaric oxygen (100% oxygen) or carbogen (95% oxygen and 5% carbon dioxide).…”
Section: Clinical Relevance Of Hypoxiamentioning
confidence: 99%
“…Over the recent decades, several hypoxia modification strategies have been developed and investigated in an attempt to improve patient outcomes (reviewed by Horsman et al [ 35 ]), however, most reported improvements in outcomes are modest due to the heterogeneity in hypoxia distribution, lack of hypoxia assessment and poor patient selection and stratification in clinical studies [ 14 , 36 ]. One early approach aimed to increase oxygen delivery to tumours by allowing patients to breathe hyperbaric oxygen (100% oxygen) or carbogen (95% oxygen and 5% carbon dioxide).…”
Section: Clinical Relevance Of Hypoxiamentioning
confidence: 99%
“…The most relevant approach to overcome tumour hypoxia is to promote oxygen delivery. Hyperbaric oxygen (HBO) treatment consists of breathing 100% oxygen at 2-4 times the normal atmospheric pressure, which results in saturated haemoglobin and increased oxygen in the circulation [5][6][7]. While HBO is applied during or briefly before the radiation treatment, multiple clinical studies, including multi-centre randomised trials by the medical research council (MRC) in late 1970s and mid-1980s, showed that HBO treatment improved local control in patients with head and neck squamous cell carcinoma (HNSCC) or cervical cancer, compared to normal air.…”
Section: Carbogen Breathingmentioning
confidence: 99%
“…The tumor cell microenvironment possesses unique characteristics such as acidic pH, hypoxia, overexpressed reactive oxygen species, and reactive sulfur species, 1 which are closely related to the growth, invasion, and metastasis of tumor cells. 2 The dynamic nature of this complex cell microenvironment causes difficulties in efficiently treating cancer. For example, overexpressed H 2 O 2 can induce a high level of reactive oxygen species in cells, which causes cell necrosis or oxidative stress.…”
Section: ■ Introductionmentioning
confidence: 99%